Consensus, Disagreement, and the Criteria of Authenticity - Archer, Joel (Journal for the study of the historical Jesus, 2025)
Recent scholarship has challenged the use of the so-called ‘criteria of authenticity’ in historical Jesus studies. One common argument draws attention to the fact that those who employ the criteria have produced an abundance of radically incompatible portraits of Jesus. The failure to generate any significant consensus in Jesus studies is therefore attributed to the criteria themselves. In response, I distinguish three versions of this line of reasoning, and I argue that none is persuasive. Scholarly disagreement, I argue, is ubiquitous across academic fields, and historical Jesus studies is not unique in this respect. There may be compelling reasons to discard or downplay the criteria of authenticity, but scholarly disagreement is not among them.